The Effect of Gamification in Computer Science Learning on Student Motivation and Learning Outcomes at SMP Negeri 27 Padang - Yulirismayenti; Dedy Irfan; Titi Sri Wahyuni; Refdinal; Ahmaddul Hadi; Abdul Habib Arrasyidi Desky (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to examine the effect of gamification in Informatics learning on students’ motivation and academic achievement in Grade VII at SMP Negeri 27 Padang. A quasi-experimental method was employed with two groups: an experimental class using gamification and a control class using conventional teaching, involving 64 students. The results show that gamification significantly enhances both motivation and learning outcomes. The average pretest score in the experimental class increased from 66.37 to 85.00 in the posttest, while the control class rose from 66.43 to 75.23. Statistical analysis revealed a significance value of 0.000 < 0.05, indicating a significant difference between the two groups. The findings suggest that incorporating gamification elements such as points, badges, and challenges creates a more engaging and effective learning environment. In conclusion, gamification serves as an innovative pedagogical strategy to address low motivation and achievement in Informatics education, aligning with the characteristics of 21st-century digital-native learners.